Tea time for the traditionally built [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2009)
Precious Ramotswe uses her formidable detection talents to track down her tiny white van--sold by her estimable husband Mr. J. L. B. Matekoni, and stolen from its new owner--while simultaneously helping to explain the dreadful losing streak of a local football team and smoothing out a snag in Mma Makutsi's engagement to Mr. Phuti Radiphut.